Food Waste Management Challenges and Strategies in The Hotel Industry in Jakarta - Andra Aditya; Kurniawati Kurniawati (Journal of Social Research, 2023)
This study aims to analyze the management of food waste in the hotel sector with a focus on reducing the amount of food waste produced. The research method used is a qualitative method with the Miles and Huberman Model approach. Primary data was obtained through in-depth interviews with 22 respondents from FnB hospitality practitioners, experts, customers, and Foodbank institutions, using a purposive sampling technique. The results show that food processing in the hotel sector is carried out efficiently, but there are differences in the number of food waste per customer. Challenges in Food Waste Management (FWM) include unpredictable sales fluctuations, lack of customer awareness, and food wastage. Effective strategies to reduce food waste involve inventory management, employee training, customer education, and collaboration with Foodbank institutions. FWM has significant economic, social, and environmental impacts. FWM has direct links to the three Sustainable Development Goals (SDG 2, SDG 12, and SDG 13) on eradicating hunger, responsible consumption and production, and climate action. Managerial implications for hotels based on these conclusions include implementing an effective monitoring and reporting system related to FWM, collaboration with Food Rescue agencies, and encouraging customer participation through education and incentives. To reduce food waste and support sustainable development goals.